Peningkatan Semangat Belajar Siswa Sekolah Dasar melalui Pembelajaran Berbasis Proyek - Aprillia Aprillia; Ibnu Muthi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to enhance elementary school students' learning enthusiasm in mathematics through the implementation of the Project-Based Learning (PjBL) approach. The background of this research is the low motivation among students, caused by the dominance of conventional, teacher-centered teaching methods, limited active student engagement, and abstract, non-contextual learning materials. This study employs a descriptive qualitative approach, using observation, documentation, and literature review as data collection techniques. The research subjects were elementary school students engaged in mathematics learning through project-based activities. One of the implemented projects was the creation of a measuring tool made from recycled materials, designed to be relevant to students’ daily lives and aligned with the learning objectives of the Merdeka Curriculum. The data were analyzed using data reduction, narrative presentation, and conclusion drawing techniques, with validity ensured through source and method triangulation. The results indicated a significant increase in students' learning enthusiasm, as reflected in the questionnaire scores which rose from 65 to 83, along with improvements in indicators such as curiosity, enthusiasm, collaboration, and self-confidence. PjBL proved effective in fostering students’ intrinsic motivation by offering autonomy, authentic projects, active collaboration, and constructive feedback. Despite challenges such as time management, limited resources, and varying group participation levels, the implementation of PjBL succeeded in creating a more meaningful, enjoyable, and contextual learning environment. This study recommends broader adoption of PjBL in elementary mathematics education as a strategic effort to improve the quality of teaching and learning.